Life-cycle assessment of forest harvesting and transportation operations in Tennessee. (1st March 2018) - Abbas, Dalia; Handler, Robert M.
Abstract: A life-cycle assessment study of roundwood supply chain activities occurring within the state of Tennessee was performed, in an effort to quantify the environmental impacts associated with wood harvest and transport operations. Statewide data from a survey given to Tennessee forest industry operators was used to construct representative primary life cycle input datasets that are unique to the industry profile within the state. This data was combined with inputs and assumptions from other relevant reports and publications to fully characterize the supply chain. Results of the life cycle assessment study indicated that greenhouse gas emissions and fossil energy demand per green tonne of wood were lower for chainsaw-based harvesting systems compared to feller buncher-based harvesting, because the relatively low harvest productivity of the chainsaw systems was more than made up for by the low inputs of fuels, lubricants, and machinery for this system. Transport of roundwood by truck resulted in transport impacts that were nearly as large as harvesting impacts, assuming a 150-km roundtrip based on Tennessee survey data. Results of this supply chain study can help the state of Tennessee understand the environmental impacts associated with traditional forest products industry operations, and guide development of new bio-based products, where environmental performance will be a key driver of successful development and implementation. Highlights: A survey instrument was used to collect primary data from loggers in Tennessee. A life cycle assessment of roundwood harvesting and transportation was constructed. Impacts of chainsaw-based harvesting were lower than harvests with feller bunchers. Transportation impacts were nearly equivalent to harvesting impacts.